Strategies for improving survival in patients with severe sepsis - Mayorga Espichán, Manuel (2010)
Sepsis is a syndrome complicating any severe infection, and it is triggered by a variable systemic host response, leading to generalized tissue damage. Sepsis does not have a characteristic clinical picture, and its diagnosis is based in a high suspect index and the verification of some general, inflammation, hemodynamic, organic dysfunction, and tissue perfusion parameters. Mortality rates in affected patients may be greatly reduced using aggressive measures during the first 6 hours after admission, starting antibiotics in the first hour after admission, using low-dose steroids in patients with refractory shock during the first 24 hours, maintaining normal blood sugar levels after ICU stabilization in post-surgical patients, using mechanical ventilation with a pulmonary protection strategy in patients with ARDS and the administration of rh-APC (recombinant human activated protein C) in selected patients.